EDIL3 and VEGF Synergistically Affect Angiogenesis in Endothelial Cells - Niu X; Li X; Feng Z; Han Q; Li J; Liu Y; Zhang K (Dove Medical Press, 2023)
Xuping Niu,1 Xinhua Li,1 Zhipeng Feng,2 Qixin Han,1 Juan Li,1 Yanmin Liu,1 Kaiming Zhang1 1Shanxi Key Laboratory of Stem Cells for Immunological Dermatosis, Institute of Dermatology, Taiyuan Central Hospital of Shanxi Medical University, Taiyuan, Shanxi, People's Republic of China; 2Department of Gastroenterology, Taiyuan Central Hospital of Shanxi Medical University, Taiyuan, Shanxi, People's Republic of ChinaCorrespondence: Kaiming Zhang, Email zhangkaiming@sina.comBackground: Angiogenesis is one of the histologically predominant characteristics of psoriasis. Vascular endothelial growth factor (VEGF) and epidermal growth factor-like repeats and discoidin I-like domains 3 (EDIL3) have critical effects on angiogenesis. Both these proteins are vital proangiogenic factors in tumor occurrence and progression; however, the relationship between EDIL3 and VEGF with psoriasis remains unclear.Objective: We aimed to elucidate the role of EDIL3 and VEGF and the involved mechanisms in psoriasis-associated angiogenesis.Methods: EDIL3 and VEGF expression in cutaneous tissue was determined by immunohistochemical assay. The effects of EDIL3 on VEGF, VEGFR2, and the growth, migration, and tube formation of human umbilical vein endothelial cells (HUVECs) were analyzed by Western blotting assay, cell counting kit-8 assay, Transwell assay, and Matrigel tube formation assay.Results: EDIL3 and VEGF levels in psoriatic lesions significantly increased as compared to those in normal individuals and showed a positive relationship with the Psoriasis Area and Severity Index. The downregulation of EDIL3 decreased VEGF and VEGFR2 expression in HUVECs. Moreover, the decreased expression of EDIL3 and VEGF reduced the growth, invasion, and tube formation abilities of HUVECs, while EDIL3 resistance to VEGF and VEGFR2 was restored by using the EDIL3 recombinant protein.Conclusion: These results suggest that psoriasis is also characterized by EDIL3 and VEGF-mediated angiogenesis. Thus, EDIL3 and VEGF could serve as novel targets for treating psoriasis.Keywords: psoriasis, angiogenesis, EDIL3, VEGF, endothelial cells